Das perdas afetivas aos ganhos reflexivos: letramento e formação leitora com contos de Lygia Fagundes Telles - Almeida , Jurema Avelino de (2021)
This work proposal had been elaborated for application in 9th grade classes, of elementary school. In it, we offer literary literacy actions with a view to training critical readers and aware of their subjective and social reality. For that, we emphasize, as praxis, the shared, pleasurable and reflective reading, as a social practice and school duty, exploring the power that literature has to humanize us and connect us with life and the world. Our enterprise arose from the experiences shared with the students, their concerns about the “losses” inherent in life. In some stories by Lygia Fagundes Telles, we find stories that make this work possible, in addition to promoting accessible and active literary literacy for these young people, also bringing current elements that interact and propagate conceptions characteristic of the human condition: “Venha ver o pôr do sol”, “Natal na barca”, “Biruta” and “O Menino”. Such narratives are fundamental elements for the execution of the proposal and, added to them, we will resort to other complementary texts, in addition to films and music, in order to substantiate a proficient and significant intervention. As a theoretical foundation, for the fields of literature and literary literacy, we have, among others, the works of Abreu (2006), Candido (1995), Cosson (2019), Dalvi (2013), Lajolo (2002), Pound ( 2006), Zilberman (2009) and, for some considerations about the tale, Bosi (2015), Cortázar (1999), Moisés (2006), Soares (2007). The methodology is based on the basic sequence, by Cosson (2019). The research will be in line with the National Common Curricular Base (BNCC), it will be of a qualitative nature, of the bibliographic research type. Due to a pandemic, we are unable to implement the proposal. Thus, the product of our work is a pedagogical notebook (itinerary notebook for literary reading) that brings together actions for the future application of the teacher proposing this work and for other professionals in the field. It is easily adaptable for possible dismemberments, according to the interest of any mediators who wish to put it into practice.